Ethylene glycol monomethyl ether research- My contribution - Oluwatoyin Adeyemo-Salami (Archive of Urological Research - Peertechz Publications, 2020)
Ethylene glycol monomethyl ether (EGME) is an industrial solvent that has wide application, including the aviation sector. It has been investigated scientifically to determine its effect on various body fluids and organs, especially the male reproductive organ. This is a review of research studies carried out using EGME with emphasis on the reproductive organs, and my investigations conducted with the solvent and in combination with a herb. Since EGME is an industrial solvent, care should be taken when exposed to it and in the presence of herbal treatments.